UNIVERSITY NOTES. - Kerrigan, Harry D. (The Accounting Review, 1940)
The article presents information on recent developments related to accounting in various universities of the United States. S. Paul Garner, associate professor of accounting, has collaborated with professor G.H. Newlove of the University of Texas in the writing of a text entitled Elementary Cost Accounting, which is expecting to get published in January 1941. Chester K. Knight, professor of accounting, and currently secretary of the Alabama Society of C.P.A.'s, will address the Birmingham, Albama chapter of the National Association of Chartered Accountants next February. Professor E.J. Kirkham of the University of Illinois, and professor Ray Sadler of the University of Indiana, has received appointments as instructors in accounting. J.M. Charitori, instructor, has resigned to become an officer of the United States Army. The University of Southern California, Los Angeles, California sponsored its second annual accounting institute on November 7, 1940. The general theme was Clarity, Brevity, and Realism in Reporting. Speakers, including participants as leaders of round tables, numbered well over thirty, and represented many lines of industry operating in the Los Angeles area.